Changes of cholinesterase activities in the plasma and some tissues following administration of L-carnitine and galanthamine to rats - Bajgar, Jiří; Bartošová, Lucie; Fusek, Josef; Svoboda, Zbyněk; Herink, Josef; Květina, Jaroslav; Palička, Vladimír; Živný, Pavel; Bláha, Václav (Neuroscience letters, 2007)
Changes of acetylcholinesterase (AChE) activities in the hypophysis and brain (frontal cortex, hippocampus, medial septum and basal ganglia), and butyrylcholinesterase in plasma and liver following galanthamine (GAL) administration were studied in rats pretreated with L-carnitine (CAR). Following only GAL administration (10 mg/kg, i.m.), both cholinesterases (without clinical symptoms of GAL overdosage) were significantly inhibited. Pretreatment with CAR (3 consecutive days, 250 mg/kg, p.o.) followed by GAL administration showed higher AChE inhibition in comparison with single GAL administration. However, a statistically significant difference was observed for AChE in the hippocampus only. The activity of peripheral cholinesterases was not influenced by CAR pretreatment. Thus, pretreatment with CAR enhanced AChE inhibition in some brain parts of the rat following GAL administration.
Keywords: lineární modely; mozek; Carnitine; lékové interakce; cholinesterasy; Dose-Response Relationship, Drug; financování organizované; krysa rodu Rattus; Financing, Organized; zvířata; Enzyme Activation; vitamin B komplex; potkani Wistar; cholinesterasové inhibitory; Drug Interactions; Rats, Wistar; butyrylcholinesterasa; Cholinesterases; galantamin; Male; karnitin; Vitamin B Complex; Brain; Linear Models; Rats; vztah mezi dávkou a účinkem léčiva; Animals; aktivace enzymů; mužské pohlaví; Butyrylcholinesterase; Galantamine; Cholinesterase Inhibitors